The Impact Of Easy Pay Later, Lifestyle, And Impulse Buying On Consumptive Behavior In An Islamic Economic View - Maulana Aksan Aksan; Reni Ria Armayani Hasibuan; Purnama Ramadani Silalahi (UNIVERSITAS PAKUAN, 2024)
Abstract. This research aims to determine the influence of ease of pay later, lifestyle and impulse buying on student consumptive behavior from an Islamic economic perspective. This research is quantitative research using multiple linear analysis. The population in this study were FEBI UINSU North Sumatra students. The sample in the research was carried out through probability sampling so that 98 respondents were obtained. Data sources were obtained through primary and secondary data. The research results show that the use of pay later, lifestyle and impulse buying significantly influence the consumer behavior of students at the Faculty of Islamic Economics and Business (FEBI) of the North Sumatra State Islamic University (UINSU). The ease of use of the pay later system encourages students to make unplanned purchases, while lifestyles influenced by social trends encourage them to buy goods that are not in accordance with their actual needs. The combination of both with impulsive shopping tendencies results in excessive and unplanned spending. In Islamic law, pay later is said to be usury because there are additional costs involved in the transaction. So pay later is prohibited in Islam according to MUI Fatwa No. 117/DSN-MUI/II/2018 and Surah Ar-Rum Paragraph 39.